Energy matrices, exergoeconomic and enviroeconomic analysis of air-cooled and water-cooled solar still: Experimental investigation and numerical simulation. (June 2021) - Shoeibi, Shahin; Rahbar, Nader; Esfahlani, Ahad Abedini; Kargarsharifabad, Hadi
Abstract: The impact of using air and water cooling glass in the double slope solar still have been performed numerically and experimentally. The thermoelectric modules cold side cools a water flow which passes on the glass cover in the water-cooled solar still. On the other hand, the wind velocity was used to cooling the glass cover in the air-cooled solar still. The convection heat transfer coefficient is accounted as boundary conditions of the glass surface. Results show that the good agreement was obtained between numerical model and experimental data. The water productivity in water-cooled solar still was 81.1% more than an air-cooled solar still. Moreover, the effects of glass cover thickness, velocity and temperature of the water cooling glass on performance of a water-cooled solar still are performed. The output results, compared to water-cooled solar still, showed that this modification of water-cooled solar still increases the water productivity by 21.53%. Also, the cost analysis indicated that the cost of produced water for water-cooled and air-cooled solar still were about 0.243 /L and 0.277 /L, respectively. Based on the results, the CO2 mitigation of air-cooled, water-cooled and modified water-cooled solar still were about 7.75, 13.09 and 16.27 tons, respectively. The enviroeconomic and exergoenviroeconomic parameters in the modified water-cooled solar still were improved by 24.3% and 632.1%, respectively, compared to the water-cooled ones. Highlights: Comparing air-cooled and water-cooled solar still using CFD and 3-E analysis. CFD modelling of water flow on the glass cover of a double-slope solar still. Improving the solar still performance was performed using CFD and 3-E analysis. Modified water-cooled solar still increases the water productivity by 21.53%. The modified system has 24.3% better performance in CO2 mitigation.